2015
DOI: 10.1002/cne.23764
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic innervation of the heart in zebrafish (Danio rerio)

Abstract: In the vertebrate heart the intracardiac nervous system is the final common pathway for autonomic control of cardiac output, but the neuroanatomy of this system is not well understood. In this study we investigated the innervation of the heart in a model vertebrate, the zebrafish. We used antibodies against acetylated tubulin, human neuronal protein C/D, choline acetyltransferase, tyrosine hydroxylase, neuronal nitric oxide synthase, and vasoactive intestinal polypeptide to visualize neural elements and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 79 publications
7
79
0
Order By: Relevance
“…In a previous study (57), we described the basic structure of the ICNS in zebrafish, which is consistent with that of humans and other mammalian models (28,33,37,43,44). The isolated zebrafish heart thus has technical advantages that may be exploited to better understand the role of the ICNS in modulating chronotropy (57).…”
Section: New and Noteworthysupporting
confidence: 71%
See 1 more Smart Citation
“…In a previous study (57), we described the basic structure of the ICNS in zebrafish, which is consistent with that of humans and other mammalian models (28,33,37,43,44). The isolated zebrafish heart thus has technical advantages that may be exploited to better understand the role of the ICNS in modulating chronotropy (57).…”
Section: New and Noteworthysupporting
confidence: 71%
“…In zebrafish and mammalian species, HCN4 channels contribute a major portion of the diastolic depolarizing current in cardiac pacemaker cells (28,33,37,43,44). Immunohistochemical evi-dence also shows that juxta-pacemaker terminals contain the neurotransmitters acetylcholine (ACh; parasympathetic, cardio-inhibitory) and norepinephrine (NE; sympathetic, cardioexcitatory), providing the neuroeffector substrate for bidrectional autonomic control of pacemaker rate (57). At the atrioventricular region (AVR) a subpopulation of HCN4-expressing cells has been identified (57).…”
Section: New and Noteworthymentioning
confidence: 99%
“…These results are similar to those of a previous study utilizing scanning electron microscopy [Sakata et al, 2001]. To observe the innervation of the taste buds, we performed double immunohistochemistry with anti-calretinin and anti-acetylated tubulin antibodies; the later marks nerve fibers [Hagströme and Olsson, 2010;Stoyek et al, 2015]. Acetylated tubulinir nerve fibers formed polygonal networks bellow the barbel epithelium ( Fig.…”
Section: Distribution Of the Taste Buds And Their Innervationsupporting
confidence: 71%
“…However, there is no direct evidence as yet for the presence of HO-1 in the pacemaker cells of the mammalian heart. In zebrafish, the cardiac pacemaker cells are located at the sinoatrial boundary (Tessadori et al, 2012;Stoyek et al, 2015). In this study, we found evidence that HO-1 is located in the presumptive pacemaker cells of the developing zebrafish heart.…”
Section: Presence Of Ho-1 In the Hearts Of Fishsupporting
confidence: 51%